Peran Dewan Pengawas Syariah Dalam Meningkatkan Transparansi Laporan Keuangan - Dewi Anhavia (Jaanur Elbarik Indonesia, 2026)
This study aims to analyze the implementation of the Sharia Supervisory Board's role in enhancing financial reporting transparency in Islamic financial institutions in South Kalimantan Province, identify the supporting and inhibiting factors affecting supervisory effectiveness, and develop a conceptual model of Sharia supervisory implementation. This study employed a qualitative approach using a field research design. Informants were selected purposively and consisted of Sharia Supervisory Board members, branch managers, operational managers, internal auditors, Sharia compliance officers, and financial reporting staff. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. The findings indicate that Sharia supervision is implemented continuously through contract monitoring, Sharia compliance evaluation, and coordination with management to follow up supervisory recommendations.